Profile, challenge, and opportunity of environmental literacy research in Indonesia: A systematic literature review - I Made Surya Hermawan; I Made Diarta; Putu Ayu Paramita Dharmayanti (University of Muhammadiyah Malang, 2024)
Systematic overview of environmental literacy research in Indonesia is a crucial aspect for determining effective strategies for strengthening environmental literacy, unfortunately, this is not widely available, especially regarding research published in Indonesia. This research aims to reveal the profile, challenges, and opportunities for strengthening environmental literacy in Indonesia. SLR was used in this research by analyzing 36 articles that met the requirements collected from journals registered by Sinta in 10 years. The articles were then analyzed using a content analysis observation sheet. This research showed fluctuations and stagnation in the number of publications. Variations in design, subjects, instruments, and data analysis techniques are also revealed. Important research results also provide interesting findings in environmental literacy profiles, types of schools, and educational curricula. Based on this, researchers in Indonesia have the challenge of increasing the number of environmental literacy research published in Indonesia. This challenge becomes an opportunity to conduct qualitative and mixed-method research involving students at various education levels. Triangulation data analysis is also important. Furthermore, implementing the Adiwiyata curriculum and innovative learning using local wisdom has the potential to strengthen students' environmental literacy. This research provides an overview for other researchers to formulate effective strategies to improve environmental literacy.